Financial market volatility: Informative in predicting recessions - Jan Annaert; Marc J.K. De Ceuster; Nico Valckx (Bank of Finland, 2001)
It is commonly agreed that the term spread and stock returns are useful in predicting recessions.We extend these empirical findings by examining interest rate and stock market volatility as additional recession indicators.Both risk-return analysis and the theory of investment under uncertainty provide a rationale for this extension.The results for the United States, Germany and Japan show that interest rate and stock return volatility contribute significantly to the forecasting of future recessions.This holds in particular for short term predictions.
URN:NBN:fi:bof-20140807308
Keywords: 330; business cycles; stock market volatility; interest rate volatility; probit model